2016
DOI: 10.1088/0957-4484/27/32/325702
|View full text |Cite
|
Sign up to set email alerts
|

Origin of blue photoluminescence from colloidal silicon nanocrystals fabricated by femtosecond laser ablation in solution

Abstract: We present a detailed investigation into the origin of blue emission from colloidal silicon (Si) nanocrystals (NCs) fabricated by femtosecond laser ablation of Si powder in 1-hexene. High resolution transmission electron microscopy and Raman spectroscopy observations confirm that Si NCs with average size 2.7 nm are produced and well dispersed in 1-hexene. Fourier transform infrared spectrum and x-ray photoelectron spectra have been employed to reveal the passivation of Si NCs surfaces with organic molecules. O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 33 publications
(39 reference statements)
1
10
0
Order By: Relevance
“…Figure 4(c) shows that the photoluminescence peak at 726 nm disappeared. The disappearance of this photoluminescence peak may improve the optoelectronic performance of the solar cells [37][38][39].…”
Section: Photoluminescence Properties Of Tio 2 Thin Film and Tio 2 -P...mentioning
confidence: 99%
“…Figure 4(c) shows that the photoluminescence peak at 726 nm disappeared. The disappearance of this photoluminescence peak may improve the optoelectronic performance of the solar cells [37][38][39].…”
Section: Photoluminescence Properties Of Tio 2 Thin Film and Tio 2 -P...mentioning
confidence: 99%
“…Very recently, we successfully fabricated stable blueemitting colloidal Si NCs in 1-hexene through a femtosecond (fs) LAL technique and demonstrated that the surfaces of the colloidal Si NCs have been well passivated by carbon chains as confirmed by Fourier transform infrared (FTIR) and x-ray photoelectron spectroscopy (XPS) spectra. The blue luminescence from colloidal Si NCs is attributed to the radiative recombination of the excitons formed at X or Γ (Γ 25→ Γ′ 2 ) point via the surface states associated with the Si-C or Si-C-H 2 bonds [14]. Then, we carried out investigation on the effect of laser fluence on the structure and optical properties of colloidal Si NCs fabricated in 1-octadecence using fs laser ablation under different laser fluences.…”
mentioning
confidence: 99%
“…The preparation procedure of colloidal Si NC solution was described in detail in our previous works [14,15]. In brief, the laser ablation experiments were carried out by using a Ti:sapphire fs laser system operated at 800 nm, with a pulse duration, laser fluence and frequency of 100 fs, 1.0 mJ cm −2 and 80 MHz, respectively.…”
mentioning
confidence: 99%
See 2 more Smart Citations